Principal Leadership in Improving Performance of Educators (Teachers) at SMPN 2 Selaawi, Garut Regency - Sopyan; Syukri Illahi; Dede Aji Mrdani (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
This research examines the important and strategic role of the main duties and functions (tupoksi) of school principals in improving the performance of teaching staff. The main point of this research is the leadership strategies used by school principals and their impact on the performance of teaching staff in educational units. By using a qualitative research method that uses questionnaire instruments, observation, and is equipped with data analysis in the form of a Teacher Performance Assessment Tool (PKG), this research provides quite in-depth insight into the importance of effective and efficient leadership strategies in order to support the realization of optimal teaching staff performance. in the school environment.